Asuhan Keperawatan Pada Pasien Dengan Hipertensi Diruangan Interne Rsud Prof. H. M. Yamin, S. H Pariaman - Adek Wulan Safitri; Kheniva Diah Anggita; Linda Marni; Aulia Asman (CV. ITTC INDONESIA, 2026)
Hypertension is often dubbed the